Indonesia and the Philippines small claims: similarities and differences - Glenda E. Feliprada,; Jayum Jawan, (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2019)
Small Claims Courts of Indonesia and Philippines conducted hearings for speedy disposition of cases where defendant failed to meet obligations on loan. The litigation does not need legal counsel, thus it is low cost and has jurisdiction over civil cases. Indonesia’s high percentage of judgment default of the corporation plaintiff defeats the goal of assisting the poor and marginalized sectors of society. On the other hand, in the Philippines, the large number of compromised agreement is an indicator of meeting the goal of assisting the poor. Arriving at a compromise requires efforts and time in negotiations that results in the reduction of payment rates and in an instalment mode of repayment. The inclusion of writ of execution to litigate default of payment is commendable while in Indonesia parties have no legal mechanism to enforce default payment of the defendant which is a weakness or limitation of legal procedure. The issues that need to be addressed by both countries include lack of public information and the strict implementation of usury law against exorbitant interest rates. Indonesia’s extrajudicial settlement and writ of execution need to be included in the Small Claims mechanism. The absence of writ execution renders the result useless.